Increased Internet Searches for Insomnia as an Indicator of Global Mental Health During the COVID-19 Pandemic: Multinational Longitudinal Study - Lin, Yu-Hsuan; Chiang, Ting-Wei; Lin, Yu-Lun (JMIR Publications, 2020)
BackgroundReal-time global mental health surveillance is urgently needed for tracking the long-term impact of the COVID-19 pandemic. ObjectiveThis study aimed to use Google Trends data to investigate the impact of the pandemic on global mental health by analyzing three keywords indicative of mental distress: "insomnia," "depression," and "suicide." MethodsWe examined increases in search queries for 19 countries. Significant increases were defined as the actual daily search value (from March 20 to April 19, 2020) being higher than the 95% CIs of the forecast from the 3-month baseline via ARIMA (autoregressive integrated moving average) modeling. We examined the correlation between increases in COVID-19-related deaths and the number of days with significant increases in search volumes for insomnia, depression, and suicide across multiple nations. ResultsThe countries with the greatest increases in searches for insomnia were Iran, Spain, the United States, and Italy; these countries exhibited a significant increase in insomnia searches on more than 10 of the 31 days observed. The number of COVID-19-related deaths was positively correlated to the number of days with an increase in searches for insomnia in the 19 countries (ρ=0.64, P=.003). By contrast, there was no significant correlation between the number of deaths and increases in searches for depression (ρ=-0.12, P=.63) or suicide (ρ=-0.07, P=.79). ConclusionsOur analysis suggests that insomnia could be a part of routine mental health screening during the COVID-19 pandemic.